2001
DOI: 10.2214/ajr.176.5.1761191
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Inversion Sonography During the Liver-Specific Late Phase of Contrast Enhancement

Abstract: Contrast-enhanced phase-inversion sonography in the liver-specific phase of contrast enhancement using Levovist provides a marked improvement in the detection of hepatic metastases relative to unenhanced conventional sonography, without loss of specificity. Phase-inversion sonography was particularly advantageous in detecting small metastases and may be a competitive alternative to CT and MR imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
1
9

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(95 citation statements)
references
References 19 publications
7
78
1
9
Order By: Relevance
“…In our case, perfusional angiosonography produced results similar to those obtained with CT, as do pulse-inversion harmonic imaging techniques. [5][6][7][8] The changes in the arterial-phase enhancement pattern of hepatic metastases from colorectal carcinoma in our case did not seem to reflect changes in tumor activity. Specifically, 2 lesions that no longer exhibited arterial-phase enhancement after 6 months of chemotherapy still showed signs of progression, as did 3 other lesions that had retained the hypervascular pattern on perfusional angiosonography.…”
Section: Discussioncontrasting
confidence: 64%
“…In our case, perfusional angiosonography produced results similar to those obtained with CT, as do pulse-inversion harmonic imaging techniques. [5][6][7][8] The changes in the arterial-phase enhancement pattern of hepatic metastases from colorectal carcinoma in our case did not seem to reflect changes in tumor activity. Specifically, 2 lesions that no longer exhibited arterial-phase enhancement after 6 months of chemotherapy still showed signs of progression, as did 3 other lesions that had retained the hypervascular pattern on perfusional angiosonography.…”
Section: Discussioncontrasting
confidence: 64%
“…Contrast-enhanced ultrasound has meanwhile been evaluated for numerous organs and has been proven to have a clear role in the detection and differential diagnosis of liver lesions [7][8][9][10][11][12][13][14][15] . For this, low-MI imaging is the technique of choice since it allows the liver to be scanned in the usual way.…”
Section: Contrast-specific Imaging Techniquesmentioning
confidence: 99%
“…Some studies have found that CEUS improved sensitivity by more than 50%, and was especially helpful for metastases smaller than 10 mm [44][45]. Our recent study found that CEUS using high-frequency linear probe could detect more lesions than routine convex probe for the lesions less than 10mm in diameter and located within 60mm below liver surface (89% vs 66%, p<0.05), and combining convex and linear probe CEUS, the sensitivity for detection of small CRLMs could reach 97% when taking CECT and CEMRI as golden standard.…”
Section: Detection and Characterizationmentioning
confidence: 99%